Periodontal Disease May be Associated With the Occurrence of Diabetic Retinopathy: A Subgroup Analysis of The Survey of the Diabetes Coordination Notebook in Gifu - Horikawa, Yukio; Suzuki, Akio; Enya, Mayumi; Hashimoto, Ken-ichi; Nishida, Shohei; Kobayashi, Ryo; Ohashi, Tetsuya; Yamazaki, Futoshi; Totani, Rieko; Kobayashi, Hiroshi; Yamamoto, Mayumi; Itoh, Yoshinori; Takeda, Jun (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aims A questionnaire survey of the prevalence of diabetic retinopathy was recently conducted in Japan. A subgroup analysis to examine the association of periodontal disease with diabetic retinopathy in subjects with diabetes and prediabetes was conducted.Methods The association of the presence of periodontal disease with the occurrence of diabetic retinopathy was examined using multivariate logistic regression analysis.Results Of 27 016 subjects who completed a survey at 217 community pharmacies, 5 572 had diabetes or prediabetes, among whom 522 and 1 421 had retinopathy or periodontal disease, respectively. Therapy duration≥10 years (OR: 2.73, 95% CI: 2.17–3.43, P<0.001), periodontal disease (OR: 2.10, 95% CI: 1.68–2.62, P<0.001) and glycated hemoglobin (HbA1c) ≥ 7.0% (OR: 1.64, 95% CI: 1.32–2.04, P<0.001) were significantly associated with the occurrence of retinopathy, while retinopathy (OR: 2.11, 95% CI: 1.69–2.63, P<0.001) and therapy duration ≥10 years (OR: 1.24, 95% CI: 1.06–1.46, P=0.007) were significantly associated with the occurrence of periodontal disease. The prevalence of retinopathy was much higher in diabetic subjects with periodontal disease than in those without it (15.1% vs. 7.8%, P<0.001). Notably, the difference of prevalence of retinopathy between subjects with and without periodontal disease was statistically significant even at HbA1c 6.0–6.9% (15.2% vs. 7.3%, P<0.01).Conclusions These findings indicate that the target HbA1c level for diabetes patients with periodontal disease may be set lower than for those without it, and that regular dental visits should be prescribed for the management of periodontal disease and the prevention of diabetic retinopathy.
Keywords: diabetic retinopathy; periodontal disease; glycated hemoglobin A